Oblique propagation and temperature effects on the resonant right-hand ion beam instability - Le, Ari; Chen, Li-Jen; Wetherton, Blake; Keenan, Brett; Stanier, Adam (Frontiers in Astronomy and Space Sciences, 2023)
The resonant right-hand instability (RHI) is often the dominant mode driven by reflected ions upstream of Earth's quasi-parallel bow shock. In the tradition of Peter Gary, this paper further explores the RHI using numerical solutions of the plasma dispersion relation and nonlinear kinetic simulations, with parameters inspired by observations from NASA's Magnetospheric Multiscale (MMS) mission. Agreement is found between the ion distributions in the particle-in-cell simulations and MMS spacecraft data, which show the gyrophase bunching characteristic of the instability. The nonlinear structures created by RHI tend to be stronger when the plasma beta is lower. These structures have sizes of around 100 to 200 ion inertial lengths perpendicular to the magnetic field, presenting planet-sized disturbances to the magnetosphere. 2d and 3D hybrid particle-in-cell simulations show that modes with a range of propagation angles oblique to the magnetic field are excited, providing a ground to understand previous statistical studies of observed foreshock waves.